Linking perfectionism with moral behaviors in sport: The mediating role of burnout and moral disengagement - Stanger, N.; Jowett, G. E.; Kaiseler, M.; Williams, T. L. (Research Quarterly for Exercise and Sport, 2024)
Purpose Research has identified a range of intrapersonal variables associated with moral behaviors in sport. However, research investigating how perfectionism and burnout are associated with prosocial and antisocial behavior toward teammates and opponents in sport has received scant attention. In the present study, we address this issue by examining whether perfectionism is associated with prosocial and antisocial behavior in sport directly and indirectly via burnout and moral disengagement.